RESENHA: HIPERTEXTO NO COTIDIANO ESCOLAR. - Soares, Maria Lúcia de Amorim; Nogueira, Eliete Jussara (Debates em Educação, 2014)
GOMES, Luiz Fernando. Hipertexto no cotidiano escolar. São Paulo: Cortez, 2011, 120p.